EFFECT OF BIDARA LEAF EXTRACT (Ziziphus Mauritiana L.) ON THE FUNCTION OF THE PANCREAS OF MALE WISTAR STRAIN RATS IN REDUCING BLOOD SUGAR LEVELS - Musdayani Nasution; Ali Napiah Nasution; Maya Sari Mutia (Jurnal Teknologi Laboratorium)
Bidara leaves contain several compounds such as alkaloids, flavonoids, quercetin, phenols, routine and terpenoids which are efficacious in medicine (Gupta, et al., 2012). The flavonoid content in bidara leaves is thought to play a significant role in increasing antioxidant activity and being able to regenerate damaged pancreatic ? cells. Flavonoids are thought to also improve the sensitivity of insulin receptors, making them useful in DM conditions. This study aims to examine the effect of bidara leaf extract (Ziziphus Mauritiana L.) on the histopathology of the pancreas of male Wistar rats, a model of type II diabetes mellitus induced by alloxan. This type of research is experimental research using a pre-test and post-test control group design. This study used 24 mice which were divided into 6 groups using the extraction results used in this study were 50, 150, 300 and 500 mg/KgBW ethanol extract of bidara leaves and 1% Na-CMC made by dissolving 1 gram Na-CMC in 100 mL of hot distilled water as a negative control and positive control given. Metformin 500mg/KgBW. The results of this research are the normality test which was carried out using the Shapiro Wilk positive negative group, 50, 150, 300 and 500 mg/kgBW had normal data, had a p value > 0.05 which means the data was normally distributed. The results of the research are the p - value for each concentration group < 0.05, namely 0.02, which means that bidara leaf extract at a level of 50 mg/kgbw is effective in reducing blood sugar levels, then 0.14, which means that bidara leaf extract is effective at a level of 150 mg/KgBW. Furthermore, 0.16 means bidara leaf extract is effective with a level of 300 mg/KgBW and 0.04